Ethno-veterinary study of medicinal plants in Charkhi Dadri district of Haryana, India - Sangwan, Sunita; Rani, Jyoti; Singh, Khushboo; Rani, Deepika; Sangwan, Sangeeta; Rani, Mamta; Gaur, Asha; Lata, Kusum (Current Botany, 2023)
Ethno-veterinary medicinal plants are important as they are used extensively in many rural areas of the world where people heavily rely on traditional herbal treatments to treat their domestic animals. Indigenous herbal remedies utilized for centuries to keep animals healthy and verbally passed down through the generations. Charkhi Dadri is a district of Haryana situated in the Trans-Gangetic Plains area of India. A total of 45 distinct medicinal plants were studied from 31 families to explore their ethno-veterinary uses of which herbs comprised the majority of the plants followed by trees, shrubs, and climbers. The seeds, leaves and whole plants are the most popular plant parts used. The people can use the documentation of this native knowledge to promote the adoption of traditional methods for treating livestock problems since time immemorial. The findings of this study demonstrate the viability of traditional medicine, which primarily relies on the usage of medicinal herbs to provide for the healthcare needs of cattle in the Charkhi Dadri District of Haryana. The information gathered from the region’s livestock farmers may also utilize to manage the nation’s system for caring for livestock and enhance the quality of life in humans.